The impact of word-of-mouth sources on the relationship between brand knowledge and brand trust / Ang Chuan Lock - Ang, Chuan Lock (2016)
The idea that higher education is a valued commercial product has reached the global marketplace. The rapid growth of newly established colleges and universities in South East Asia, Middle East and North African region have intensified trade in this sector. However, Private Higher Education Institutions (PHEIs) in Malaysia still facing failure to rule it and unable to secure the most possible number of students. The failure of PHEIs has alarmed the government. Here, the enrolment of students becomes a complicated issue. Past studies suggested that the increasing of enrolment is highly possible by the dissemination of positive word-of-mouth communication (WOM) sources which greatly enhance students’ existing knowledge towards a particular PHEI and the resulting trust. Accordingly, this study examines the moderation impact of WOM communication influences towards the relationship between brand knowledge and brand trust of PHEIs. Sequential explanatory mixed method research design has been utilized in this study. Students from PHEIs in Klang Valley were approached in person to participate in the survey and a series of interviews with administrators of selected PHEIs was subsequently conducted. The quantitative analysis of this study discovered that the inclusion of influences from WOM communication sources has significantly heightened the impact of brand knowledge towards brand trust of PHEIs. Similarly, the qualitative analysis of the study further enhanced the discovery on the view of PHEIs operators. PHEIs are recommended to capitalize on the potential of effective branding and the management of WOM communication sources in order to improve student’s enrolment in their institutions.